Compact three‐way filtering Bagley polygon power divider based on composite right/left‐handed transmission lines. Issue 6 (26th March 2018) - Song, Kaijun; Xu, Boqiang; Guo, Song; Ren, Xue; Zhang, Fan
Abstract : This study presents a compact three‐way Bagley Polygon power divider integrated with bandpass response. Two compact filters are embedded into the power divider to replace the conventional quarter‐wavelength transmission lines (TLs). Moreover, the zero‐degree TLs are utilised to realise the miniaturisation, meanwhile, the power divider's intrinsic isolation performance is maintained. Analysis and guided equations are given. For verification, a Bagley Polygon power divider integrates with good filtering response and wide stopband is fabricated. Good agreement between the prediction and measurement validated the proposed method.